Enhancing refractive index of sol-gel coatings for polymeric substrates - Zheng, Yuanhuan. (2009)
Inorganic colloids TiO2 and ZnO have been successfully prepared using different “bottom up” techniques, such as Sol-gel and Solvo-thermal processes. Various characterization techniques such as XRD, DLS were employed to study the crystal phase, particle size and zeta-potential. It was discovered that TiCl4/Benzyl alcohol and ZnAC2/MeOH processes gave the smallest particle sizes of 44.97nm and 295.3nm for TiO2 and ZnO colloids respectively, while LTDRP technique produce phase pure Rutile Titania. Optical characterizations such as ellipsometry and UV-VIS spectroscopy were also conducted; to investigate the impact of colloid and coating parameters on the optical and mechanical performances of the coatings. From experimental results, it was concluded that average transmittance and refractive index of the coatings, decreased with increased in coating thickness, crystal phase, particle size and colloid concentration; while hardness of coating was dependent solely on the thickness of the thin film. To date, the highest refractive index coating was prepared using 1g of Rutile Titania with particle size of 73.78nm in a GLYMO/TEOS matrix. The properties achieved were refractive index of 1.695, average transmittance of 89.35% and a hardness of 2H.